2016
DOI: 10.2147/ceor.s109649
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of online hemodiafiltration versus high-flux hemodialysis

Abstract: BackgroundClinical studies suggest that hemodiafiltration (HDF) may lead to better clinical outcomes than high-flux hemodialysis (HF-HD), but concerns have been raised about the cost-effectiveness of HDF versus HF-HD. Aim of this study was to investigate whether clinical benefits, in terms of longer survival and better health-related quality of life, are worth the possibly higher costs of HDF compared to HF-HD.MethodsThe analysis comprised a simulation based on the combined results of previous published studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
0
22
0
4
Order By: Relevance
“…Its benefits to patient survival were first pointed out by retrospective studies [ 7–10 ] and afterwards confirmed by large randomized clinical trials like the Convective Transport Study CONTRAST study [ 11 ], the Turkish study [ 12 ] and the Estudio de Supervivencia de Hemodiafiltración On-Line (ESHOL) [ 13 ] study, whose main conclusion was that high-efficiency post-dilution OL-HDF reduces all-cause mortality compared with conventional HD, especially when higher convective volumes are achieved. Unfortunately, OL-HDF techniques are not available for every patient for different reasons, including vascular access dysfunction, water treatment systems unable to provide ultrapure water or economic problems, even though OL-HDF can be considered cost effective compared with HF HD [ 14 ]. In these situations, a novel class of membranes with a higher pore size designed to increase the removal of larger middle molecules in conventional HD, called medium cut-off (MCO) dialysers, could be promising [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its benefits to patient survival were first pointed out by retrospective studies [ 7–10 ] and afterwards confirmed by large randomized clinical trials like the Convective Transport Study CONTRAST study [ 11 ], the Turkish study [ 12 ] and the Estudio de Supervivencia de Hemodiafiltración On-Line (ESHOL) [ 13 ] study, whose main conclusion was that high-efficiency post-dilution OL-HDF reduces all-cause mortality compared with conventional HD, especially when higher convective volumes are achieved. Unfortunately, OL-HDF techniques are not available for every patient for different reasons, including vascular access dysfunction, water treatment systems unable to provide ultrapure water or economic problems, even though OL-HDF can be considered cost effective compared with HF HD [ 14 ]. In these situations, a novel class of membranes with a higher pore size designed to increase the removal of larger middle molecules in conventional HD, called medium cut-off (MCO) dialysers, could be promising [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“… 20 This may reflect the increasing implementation of HDF in European RRT units, despite continued controversy about its cost-effectiveness. 21 , 22 , 23 , 24 , 25 , 26 Previous reports have indicated that an oxalate elimination of 6 to 10 mmol/1.73 m 2 per week on standard hemodialysis (HD) is inadequate to lower P Ox ; on this regimen, predialysis P Ox values averaged approximately 45 μmol/l. 10 , 27 , 28 , 29 In search of an optimized therapeutic regimen to eliminate P Ox , 3 studies in patients with secondary hyperoxalemia 29 , 30 , 31 reported higher oxalate clearances with HDF compared with standard HD treatment ( Table 1 ).…”
mentioning
confidence: 99%
“…Some studies comparing cost-effectiveness of OL-HDF and HD reported that HD is more cost-effective; however, a recent analysis by Ramponi et al [77] showed that OL-HDF is as cost-effective as high-flux HD. An advantage over high-flux HD is the substantial effect of OL-HDF on the improvement of patient's satisfaction and QoL [78].…”
Section: Hemodialysis Versus Online-hemodiafiltrationmentioning
confidence: 99%